Towards the understanding of wheel-rail flange squeal: In-situ experiment and genuine 3D profile-enhanced transient modelling. (15th November 2022) - Luo, Yun-Ke; Zhou, Lu; Ni, Yi-Qing
Highlights: A systematic study with new insights into wheel-rail flange squeal is carried out. Well-controlled in-situ experiments are conducted for flange squeal measurements. An integrated transient model is proposed and validated for flange squeal analysis. The model intakes 3D scanning irregularity data for flange squeal reappearance. Mechanism of flange squeal is studied by discussion on identified critical factors. Abstract: Wheel-rail squeal noise during train turning has been a tricky problem influencing passengers and nearby residents. The tonal curve squeal that mainly occurs at the inner rail has been extensively studied, while the broadband flange squeal that takes place at the outer rail that can be equally annoying is seldom mentioned and hardly investigated. This paper presents a study aiming at understanding the mechanism of wheel-rail flange squeal from phenomenon to the underlying source. The study systematically demonstrates the connection between the observed wheel-rail flange squeal noise and contact force, with measurements taken from a series of well-controlled in-situ experiments on an operating metro line, and numerical simulations. An integrated transient model consisting of three submodels on train dynamics, rail dynamics, and wheel-rail contact incorporating genuine 3D surface irregularities is developed specifically for flange squeal analysis. The developed model can reproduce the characteristics of flange squeal and correlates wheel-rail contact force with the flange squeal noise with satisfactory performance. Features of flange squeal under four-speed levels corresponding to in-situ experiments are reappeared from global dynamics to local contact status. An explanation of the generation mechanism of flange squeal is proposed by measurement observation and confirmed through the proposed model with multiple influencing key factors, including train speed, contact position, shape of contact patch, contact creepages, and wheel and rail irregularities. The present study is expected to establish a footstone for the mechanism comprehension of flange squeal and inspire further research in this area.